Human adenovirus type 9 E4 open reading frame 1 encodes a cytoplasmic transforming protein capable of increasing the oncogenicity of CREF cells. - Weiss, R S (1996)
The induction of estrogen-dependent rat mammary tumors by human adenovirus type 9 (Ad9) requires the Ad9 E4 open reading frame 1 (9ORF1) protein, which alone can transform that rat embryo fibroblast cell line CREF in vitro. In the present study, independent pools of both 9ORF1-expressing and control CREF cells were generated by selection with G418 and compared with respect to transformed properties. Indirect immunofluorescence analyses revealed that more than 99% of the cells that made up the 9ORF1-transfected pools expressed 9ORF1 protein and, together with confocal laser scanning microscopy, indicated that this E4 protein was located predominantly within the cytoplasm of cells. With regard to transformation, cells of the 9ORF1-expressing pools differed from those of control pools by forming foci, displaying morphological alterations, growing more efficiently in soft agar, and reaching higher saturation densities. Following injection into immunocompetent syngeneic rats, the 9ORF1-expressing pool cells exhibited greatly enhanced oncogenicity compared with control pool cells. These results show that 9ORF1 protein (i) localizes predominantly within the cytoplasm, (ii) confers multiple general transformed characteristics to CREF cells in vitro, and (iii) increases the tumorigenic properties of these cells in vivo.